The potential of mobile health clinics in chronic disease prevention and health promotion in universal healthcare systems. An on-field experiment - Chiara Bertoncello; Silvia Cocchio; Marco Fonzo; Silvia Eugenia Bennici; Francesca Russo; Giovanni Putoto (International Journal for Equity in Health, 2020)
Abstract Background Mobile health clinics (MHCs) are recognized to facilitate access to healthcare services, especially in disadvantaged populations. Notwithstanding that in Europe a wide-ranging background in mobile screening units for cancer is shared, evidences about MHCs targeting also at other non-communicable diseases (NCDs) in universal health coverage systems are scarce. The aim of this study was to describe the population attracted with a MHC initiative and to assess the potential of this tool in prevention and control of NCDs. Methods Our MHC was set up in a railway wagon. Standard body measurements, finger-stick glucose, total cholesterol and blood pressure were recorded. Participants were asked about smoking, physical activity, diet, compliance to national cancer screening programmes and ongoing pharmacological treatment. One-to-one counselling was then provided. Results Participants (n = 839) showed a higher prevalence of overweight/obesity, insufficient intake of vegetables, sedentary lifestyle, and a lower compliance to cancer screening compared with reference population. Our initiative attracted groups at higher risk, such as foreigners, men and people aged from 50 to 69. The proportion of newly diagnosed or uncontrolled disease exceeded 40% of participants for both hypertension and hypercholesterolemia (7% for diabetes). Adherence rate to counselling was 99.4%. Conclusions The MHC was effective in attracting hard-to-reach groups and individuals who may have otherwise gone undiagnosed. MHCs can play a complementary role also in universal coverage health systems, raising self-awareness of unreached population and making access to primary health care easier.